2018
DOI: 10.3889/oamjms.2018.077
|View full text |Cite
|
Sign up to set email alerts
|

Angulated Dental Implants in Posterior Maxilla FEA and Experimental Verification

Abstract: AIM: This study aimed to evaluate the effect of different implant angulations in posterior maxilla on stress distribution by finite element analysis and verify its results experimentally. METHODS:Two simplified models were prepared for an implant placed vertically and tilted 25° piercing the maxillary sinus. Geometric models' components were prepared by Autodesk Inventor then assembled in ANSYS for finite element analysis. The results of finite element analysis were verified against experimental trials results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…11,15,39,40 Hamed et al 40 reported that im-plants tilted by 25°may be considered as an alternative to avoid additional surgery in the maxillary sinus; however, the tilted implants can increase the stress by 66% when compared to straight implants. 40 In this study, despite observing high stress in the cortical bone of models with tilted implants, the data difference was not particularly relevant when compared to straight implants. However, tilted implants increased the stress concentration area in the cortical bone, mainly in the first molar area (Fig 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…11,15,39,40 Hamed et al 40 reported that im-plants tilted by 25°may be considered as an alternative to avoid additional surgery in the maxillary sinus; however, the tilted implants can increase the stress by 66% when compared to straight implants. 40 In this study, despite observing high stress in the cortical bone of models with tilted implants, the data difference was not particularly relevant when compared to straight implants. However, tilted implants increased the stress concentration area in the cortical bone, mainly in the first molar area (Fig 2).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the FEA analysis results corroborated results of previous biomechanical studies that evaluated the effect of tilted implants. 11,15,39,40 Hamed et al 40 reported that im-plants tilted by 25°may be considered as an alternative to avoid additional surgery in the maxillary sinus; however, the tilted implants can increase the stress by 66% when compared to straight implants. 40 In this study, despite observing high stress in the cortical bone of models with tilted implants, the data difference was not particularly relevant when compared to straight implants.…”
Section: Discussionmentioning
confidence: 99%
“…Then, set of Boolean operations on ANSYS environment (ANSYS Inc., Canonsburg, PA, USA) were performed to create enamel layer, and roots cavities in bone and then finalize the model. All materials which fed to ANSYS were considered homogenous, linear and isotropic as reported by Hamed H.A 2018 (25) and listed as Young's modules [GPa] and Posison's ratio; Titanium: (110.0) (0.34), Dentine: (18.6) (0.31), Enamel: (84.1) (030), Cortical bone: (13.7) (0.30) and Cancellous bone: (1.37) (0.30) respectively.…”
Section: Methodsmentioning
confidence: 99%
“…6,11,12,16,19,27 The use of only one point in each 3D model was possible due to the use of the Autodesk Inventor ® is commonly used in bioengineering for stress and strain assessment, which requires accurate positioning of the models before mechanical analyses. 28,29 In the present research, this software was fundamental to ensure the correct positioning of the models, which is essential in studies for 3D models superimposition. Autodesk Inventor ® , as well as other CAD/CAM software, is compatible with several 2D and 3D file extensions, especially the so-called "neutral formats", such as Standard Triangle Language (STL), and Parasolid (x_t).…”
Section: Inter-and Intra-examiner Measures Showed a High Degree Of Ag...mentioning
confidence: 99%